Evaluation of organic farming as a sustainability indicator for the Akyaka region - Külçe, Gülsüme. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2013., 2013)
In recent years, there has been an increasing awareness of the need to manage the impact of human activities on the environment. Sustainable communities play an important role in developing this awareness especially on the regional basis. The aim of the study is to assess the current environmental status of the coastal town of Akyaka located in Southwest of Turkey and to develop proposals for the sustainability approach of the town with special emphasize on organic agricultural activities. Concerning the residents and visitors sustainable approach, an integrated survey was conducted among the citizens of Akyaka Region in order to assess the potential of organic farming as a sustainability indicator. The main idea behind this is to assess the state of organic farming applications and level of awareness among farmers and the degree of interest of local community in organic products. Within this respect, two separate questionnaires were prepared; one for farmers and the other one for consumers. Questionnaires were conducted with both farmers at the local marketplace and residents at restaurants, hotels of Akyaka. Moreover, 135 consumers and additional 30 farmers from the surrounding villages of Akyaka were interviewed. The number of interviewed participants corresponds to 6.6% of the total target people which is above evaluation limit of 5%. The information obtained from Organic Consumers’ Questionnaire for Akyaka Region was analyzed by using Statistical Package for the Social Sciences (SPSS, version 21.0) statistics program. On the other hand, as the current organic product information achieved by questionnaire applied for farmers contains variety of data, the results were evaluated on frequency basis of SPSS and general evaluation. In conclusion, among many areas about environmental management systems, organic farming was selected as the key topic of this thesis. The aspects of sustainability are interconnected and related to each other and understanding these relationships is crucial for successful implementation of an ecovillage concept. According to this study, income level was emerged as the main differentiator in purchasing organic products. On the other hand, age and gender of consumers and organic food purchasing have no significant correlation.
Keywords: Organic farming -- Turkey.; Organic farming -- Turkey -- Marketing.